2023
DOI: 10.3390/su15021594
|View full text |Cite
|
Sign up to set email alerts
|

Impact of E-Commerce and Digital Marketing Adoption on the Financial and Sustainability Performance of MSMEs during the COVID-19 Pandemic: An Empirical Study

Abstract: The COVID-19 pandemic has remarkably affected the business processes and performance of micro-, small-, and medium-sized enterprises (MSMEs) across the world. MSMEs have had to adopt and implement numerous strategies to sustain their businesses, and their financial and sustainability performance has been impacted by their choice of e-commerce (EC) platforms and digital marketing (DM) strategies. The objective of this research was to explore the effects of EC and DM platforms and strategies on facilitating MSME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 116 publications
5
39
0
3
Order By: Relevance
“…According to Gao et al (2023), digital marketing is the strategy of promoting products or services using digital technology such as the internet, social media, search engines, email, and mobile devices. The history of digital marketing can be traced back to its earliest days on the internet when companies began to realize the potential of using websites to reach a wider audience.…”
Section: Digital Marketingmentioning
confidence: 99%
“…According to Gao et al (2023), digital marketing is the strategy of promoting products or services using digital technology such as the internet, social media, search engines, email, and mobile devices. The history of digital marketing can be traced back to its earliest days on the internet when companies began to realize the potential of using websites to reach a wider audience.…”
Section: Digital Marketingmentioning
confidence: 99%
“…The focus on the "new normal" is crucial, but continuous updates and research will be necessary as the post-pandemic business environment evolves. Gao et al (2023) assess the impact of e-commerce and digital marketing adoption on the financial and sustainability performance of MSMEs during the COVID-19 pandemic through an empirical study. This research is valuable for its timely investigation into how digital strategies have influenced business performance in a crisis context, highlighting the resilience and adaptability afforded by digital tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Sarker et al [38] stated that SMEs that diversified their products and services had a greater chance of surviving the pandemic. Gao et al [39] found that SMEs that adopted e-commerce during the pandemic reported an increase in sales. In addition, Qamruzzaman [40] identified that SMEs' sales increased following the formation of partnerships during the pandemic.…”
Section: Whether E-commerce Platform Was Used or Not For Selling Prod...mentioning
confidence: 99%